Analysis of Recent Trends on Uzbek Migrants - Rasulov, Ikhtiyor (PT FORMOSA CENDEKIA GLOBAL, 2024)
This essay delves into the complex and multi-dimensional migration situation in Uzbekistan, examining it from both global and local perspectives. Using recent data from international organizations and national sources, it analyzes the drivers and patterns of migration, highlighting the implications of these trends for labor rights, human rights, and social equality. By employing a rigorous analytical lens, this paper critically assesses policy interventions to protect migrant workers and proposes comprehensive solutions to empower the Uzbek diaspora, safeguard labor rights, and reduce dependency on remittances